2011
DOI: 10.1177/0003122411400056
|View full text |Cite
|
Sign up to set email alerts
|

Changing Workplaces to Reduce Work-Family Conflict

Abstract: Work-family conflicts are common and consequential for employees, their families, and work organizations. Can workplaces be changed to reduce work-family conflict? Previous research has not been able to assess whether workplace policies or initiatives succeed in reducing work-family conflict or increasing work-family fit. Using longitudinal data collected from 608 employees of a white-collar organization before and after a workplace initiative was implemented, we investigate whether the initiative affects work… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
138
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 422 publications
(160 citation statements)
references
References 70 publications
5
138
0
1
Order By: Relevance
“…Hence requirements (iii) and (iv) have been fulfilled. Therefore, we conclude there is moderately strong evidence that higher global WTC [ie, a general increase of WTC (32) or introduction of self-scheduling (46,48)] causes an improvement in work-non-work balance.…”
Section: Research Questionmentioning
confidence: 80%
See 2 more Smart Citations
“…Hence requirements (iii) and (iv) have been fulfilled. Therefore, we conclude there is moderately strong evidence that higher global WTC [ie, a general increase of WTC (32) or introduction of self-scheduling (46,48)] causes an improvement in work-non-work balance.…”
Section: Research Questionmentioning
confidence: 80%
“…Only longitudinal and intervention studies meet the second requirement, with the latter providing the strongest opportunity to assess causal associations. Within the current review, three intervention studies (32,46,48) focused on the association between global measures of WTC and worknon-work balance, of which two identified a significant positive association, thereby fulfilling requirements (i) and (ii). The significant associations found are consistent with the time-and recovery-regulation mechanisms, and the occupational health theories that were outlined in the introduction.…”
Section: Research Questionmentioning
confidence: 90%
See 1 more Smart Citation
“…Literature classifies flexible work practices as office-based practices and flexi-place practices (Grobler & De Bruyn 2011); as well as flexitime and flexi-place (Munsch, Ridgeway & Williams 2014). Kelly, Moen and Tranby (2011) refer to flexibility as schedule control, because flexible work options can include contingent work, contract work and just-in-time staffing. The extent to what employees experience as flexible working hours requires supportive organisational culture (Galea, Houkes & De Rijk 2014), and it is important that management within organisations acknowledges the fact that employees go through different phases during careers and specific requirements can change (Fransman 2015).…”
Section: Flexible Workmentioning
confidence: 99%
“…In their analysis of a work place initiative to improve schedule control, Kelly, Moen, and Tranby (2011) found that the Results Only Work Environment (ROWE) initiative significantly reduced work-family conflict and that this effect was fully mediated by employee perceptions of schedule control. Taken together, the literature suggests that more control over work and scheduling has many positive effects on employees' individual health and work-family management.…”
Section: Autonomymentioning
confidence: 99%